Uji potensi faloak pada kondisi imunosupresif - heny Nitbani; Hera Maheshwari; Koekoeh Santoso (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Faloak (Sterculia quadrifida R. Br.) is an endemic plant in the Province of Nusa Tenggara Timur especially Kupang City and surrounding areas. This plant is used by local people as a traditional medicine to treat various diseases. This plant contains polyphenolic compound that have potential as an immunomodulators. This study aims to explore the potential of faloak bark ethanol extracts as an immunomodulator in adult quail (Coturnix coturnix japonica) on immunosuppression condition by measuring the leukocytes, leukocytes differential (lymphocytes, heterophils, monocytes, eosinophils, basophils). This study used a Completely Randomized Design that devided into four groups. The control group (K0) was not given faloak extracts, group KF were only given faloak extract 250 mg/kg BW orally for 28 days. Group D were given dexamethasone 0,54 mg/kg BW orally for 28 days. Groups D1 were given dexamethasone 0.54 mg/kg BW for 28 days and D2 were given dexamethasone 0.54 mg/kg BW for 14 days followed by faloak doses of 250 mg/kg BW for 14 days. Vaccination was done on day 29. Leukocytes and differential leukocytes value measured on day 14th before vaccination and day 25th after vaccination. Faloak bark ethanol extracts have potential as an immunomodulatory in adult quail on immunosuppression condition. It was indicated by increased of leukocytes, lymphocytes, heterophils and monocyte